THEMATIC PROGRESSION PATTERNS OF SHORT STORY THE BLACK CAT - Dewi Fatmawati; Tengku Silvana Sinar; Rohani Ganie; Muhammad Yusuf (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This study attempts to investigate thematic progression deployed in The Black Cat short story. The objectives of study are 1) To indicate the types of Thematic Progression in “The Black Cat” short story and 2) to describe the realization of Thematic Progression in “The Black Cat” short story. This study was conducted in descriptive qualitative design. The data were taken from the text of “The Black Cat” short story. The source of the data in this study was The Black Cat and Other Stories book written by Edgar Allan Poe. Systemic Functional Linguistics theory proposed by Halliday (1994) was used to analyzed thematic progression in “The Black Cat” short story regarded with Textual Function. In analyzing the thematic progression, there are three kinds of thematic progression: theme reiteration, the zig-zag pattern and the multiple- rheme pattern. The findings showed that the multiple- rheme pattern is the most dominant realized in 32 times (74%), theme reiteration is the second realized in 7 times (16,3%), and the zig-zag pattern is realized in 4 times (9,3%) and the least dominant pattern in “The Black Cat” short story.